(untitled) (International Journal of Engineering and Computer Science, 2025)
This article examines approaches to building fault-tolerant distributed systems while considering the constraints of the CAP theorem. It explores the impact of trade-offs between consistency, availability, and partition tolerance on architectural decisions and system performance. The study investigates real-world CAP-balancing strategies, including CP, AP, and CA models, as well as hybrid approaches that dynamically adjust consistency and availability levels based on workload characteristics and business requirements. Particular attention is given to the practical application of CAP principles in modern distributed databases, financial systems, and cloud services.